Pengaruh Nilai Tukar, Inflasi, Dan Pendapatan Nasional Terhadap Ekspor Non Migas Indonesia - Alvino Rezandy; ach Yasin (Universitas Negeri Surabaya, 2021)
This study aims to determine the effect of the exchange rate, GDP and inflation variables on the value of non-oil and gas exports in Indonesia during the 2010-2020 period. The method used in this study is multiple linear regression according to its function. It is used to see the effect between variables whose number is more than 2 variables. The data used is secondary data, the data obtained in the form of time series which is processed using statistical applications. From the regression results, it is found that the independent variable, namely the exchange rate, has a significant negative effect, inflation has no effect, while GDP has a positive and significant effect on the dependent variable, namely the value of non-oil and gas exports in Indonesia Keywords: GDP, Inflation, Exchange Rate, Export